The holes problem in wireless sensor networks a survey. - Ahmed, Nadeem
Several anomalies can occur in wireless sensor networks that impair their desired functionalities i.e., sensing and communication. Different kinds of holes can form in such networks creating geographically correlated problem areas such as coverage holes, routing holes, jamming holes, sink/black holes and worm holes, etc. We detail in this paper different types of holes, discuss their characteristics and study their effects on successful working of a sensor network. We present state-of-the-art in research for addressing the holes related problems in wireless sensor networks and discuss the relative strengths and short-comings of the proposed solutions for combating different kinds of holes. We conclude by highlighting future research directions.
Keywords: Computer Systems Organization; Computer communication networks; Network architecture and design; Wireless communication; Processor architectures; Other architecture styles; Cellular architecture (e.g., mobile).; Computer communication networks; Network protocols; Routing protocols; Design; Reliability